Truebounded, Overbounded, or Underbounded? Scientists’ Personal Publication Lists versus Lists Generated through Bibliographic Information Services - Isabelle Dorsch; Johanna M. Askeridis; Wolfgang G. Stock (Publications, 2018)
A truebounded publication list of a scientific author consists of exactly all publications that meet two criteria: (1) they are formally published (e.g., journal article or proceeding paper); (2) they have scientific, scholarly, or academic content. A publication list is overbounded if it includes documents which do not meet the two criteria (such as novels); a publication list is underbounded if it is incomplete. Are authors’ personal publication lists, found on their personal sites on the Internet or in institutional repositories, truebounded, overbounded, or underbounded? And are the respective publication lists generated through bibliographic information services truebounded, overbounded, or underbounded? As case studies, publications of nine International Society of Scientometrics and Informetrics (ISSI) Committee members (published between 2007 and 2016) were collected to create preferably complete personal publication lists according to the two criteria. We connect the “relative visibility of an author” with the concepts of truebounded, overbounded, and underbounded publication lists. The authors’ relative visibility values were determined for the information services Web of Science (WoS), Scopus, and Google Scholar and compared to the relative visibility of the authors’ personal publication lists. All results of the bibliographic information services are underbounded. Relative visibility is highest in Google Scholar, followed by Scopus and WoS.